Magyarországi hallgatók a bécsi és a krakkói egyetemen a Jagelló-korban (1491–1525) - Draskóczy, István (Gerundium, 2017)
Students from the Hungarian Kingdom at the Universities of Vienna and Krakow in the Jagiellonian Age (1491–1525). This paper aims at examining the number of the students from the Hungarian Kingdom during the period of the Jagiellonian kings in Hungary. The importance of the topic is explained by the fact that 90 percent of the students attending foreign universities matriculated at these two institutions. It can be declared that the number of those who enriched their knowledge at these two universities increasedin this period. This growth stopped in the second half of the 1510s and the number of the Hungarian peregrinators radically decreased after 1521. The phaenomenon can be explained by the Reformation. Meanwhile, the war against the Ottoman conquerors has to be mentioned in the case of the Hungarian Kingdom.